A educação de Jovens e Adultos (EJA) no sistema prisional de Uberlândia -MG - 1998 a 2011 - Resende, Jefferson Albernaz (2021)
This paper aims at presenting a Master of Education’s research in the History and Historiography areas. The main theme involves the Education Program for Youths and Adults (Educação de Jovens e Adultos - in Portuguese) inside the Brazilian Prision System, focusing on learning practices in the city of Uberlandia - Minas Gerais State. The following investigation includes the beginning of 1998 as the significant period of the inauguration of the Penal Colony Professor Jacy de Assis (Colônia Penal Professor Jacy de Assis), later named Professor Jacy de Assis Penitentiary (Presídio Professor Jacy de Assis). The construction of the first prison in the city of Uberlandia could enable to implement schooling inside such system, rights guaranteed by the Law of Penal Execution (LEP) Brazil nº 7.210, July 11th, 1984 which foresees school education for prisioners. At the end of the year 2011, on June 29th the Law nº 12.433 was approved, which altered the 1984 and the LEP might guarantee the inmate sentence reduction. Therefore, this thesis concerns mainly the investigation of the history of the Education Program for Youths and Adults in the prision system; also analysing the legislation regarding schooling practices related to such system in Brazil, Minas Gerais and Uberlandia City during the study period. For this reason, our paper seeks to comprehend historically the aforementioned program concepts and also map the proposals and developed measures from the period 1998 to 2011. Methodologically, a bibliogaphical research was carried out in order to achieve our goals, besides collecting law data refering to the regulation of the program during the research study period, and, in addition to that, accessing the Municipal Public Arquive (Arquivo Público Municipal) for a documental approach, by using the Brazilian Newspaper Jornal Correio as reference. Furthermore, it was also taken into consideration a microhistory methodological approach, which has distinguished importance in order to have knowledge of the Education Program for Youths and Adults in the prision system of Uberlandia.